NETWORK DESIGN OF THE IMPLEMENTATION OF DIGITAL TWINS IN INDUSTRY - S. Tsohla; N. Simchenko; V. Moiseenko (Вестник Северо-Кавказского федерального университета)
He article is devoted to the analysis of the priority directions of innovation in industry, highlights the trend of technological development - the implementation of digital twins. New opportunities for industrial cooperation in the conditions of digitalization and the advantages of creating a network organization of participants in the implementation of digital projects are studied. Network interaction is defined as a form of effective competitive cooperation in the development and implementation of digital counterparts in the field of industrial production. The network model of interaction is designed on a platform basis to optimize the management of the processes of creating and implementing digital twins, efficient distribution and use of resources of cooperation participants, and the production of competitive industrial products.